The Effect of AlTi5B1 and ALTAB Ti80 with a Combination of AlSr15 and Mg Additions on Strength and Ductility of A356 Aluminum Alloys - Mostavan, Afghany; Setiawan, Asep Ridwan; Basuki, Arif; Ardy, Husaini (Metalurgi, 2023)
The current study aims to analyze microstructural changes affecting the A356 aluminum alloy, a hypoeutectic Al-Si-Mg alloy. This aluminum alloy is well-known for its strength, resistance to corrosion, lightweight, and heat treatability. The main objective of this research is to improve the strength and ductility of A356 alloys by using a synergistic strategy that includes AlTi5B1 and ALTAB Ti80 for microstructural alteration in combination with AlSr15 and Mg. The experimental results show that including all constituents in the as-cast condition enhances the ultimate tensile strength and elongation. Furthermore, in the heat-treated state, the addition of ALTAB Ti80 effectively maintains tensile strength (σuts=233.7 MPa), yield strength (σy=180.3 MPa), and elongation (e=5.8%). Additionally, when combined with Mg, the tensile strength and yield strength exhibit further improvement (σuts=253 MPa and σy=215.7 MPa); however, elongation is significantly reduced (e=2.7%)